Premature Cardiovascular Disease in Women with Lupus and Relationship to Disease Severity - Patricia Dhar, J.; Levy, Phillip; Essenmacher, Lynnette; Ager, Joel; Chiodo, Lisa; Schultz, Daniel; Stark, Azadeh; Schwartz, Ann; J. Sokol, Robert (Current Women's Health Reviews, 2013)
Introduction: Premature onset of cardiovascular disease (CVD) in women with systemic lupus erythematosus (SLE) seems to involve both traditional Framingham risk factors as well as lupus-specific factors. We assessed the risk of cardiovascular disease in premenopausal women with lupus and any relationship of cardiovascular disease to disease severity and history of pregnancy hypertensive complications. Methods: Female patients in this study with a confirmed diagnosis of lupus were obtained from the Wayne State University Database. We used chi-square analysis to assess the effect of 2 suspected risk factors (lupus disease severity and hypertensive complications during pregnancy [i.e., eclampsia/pre-eclampsia]) on cardiovascular (myocardial infarction [MI], transient ischemic attack [TIA], and chronic hypertension [HTN]) and metabolic (hyperlipidemia [HL] and diabetes mellitus [DM]) disease rates. To quantify the degree of excess risk in SLE patients, we used a Z test for proportions with population frequencies from the National Health and Nutrition Examination Survey (NHANES) database as the comparator and calculated risk ratios (RR) for specific cardiovascular and metabolic diseases among pre- and postmenopausal women [29, 30]. Results: Mean age of the cohort was 33 years at time of lupus diagnosis, 343 (50.6%) were premenopausal, 310 (45.8%) had severe SLE, and 25 (3.7%) had pregnancy hypertensive complications. Chi Square analysis showed statistically significant increases in both cardiovascular and metabolic diseases in women with severe SLE. Among those with hypertensive complications during pregnancy, the only significant association was the development of chronic HTN (p<0.01). For cardiovascular risk, we focused on the 343 premenopausal women. Premenopausal women with SLE were at significantly increased risk for myocardial infarction [MI] (RR=5.50), hypertension [HTN] (RR=1.22), transient ischemic attacks [TIA] (RR=4.38), and hyperlipidemia (RR=1.9). Conclusion: Women with SLE are at increased risk for premature cardiovascular disease compared to the general population. Increased risk for cardiovascular disease appears greatest for women with severe lupus indicating a potential dose/response relationship. Premenopausal women with severe SLE should be monitored closely for cardiovascular disease.
Keywords: lupus